A nursing care of patients after cardiac arrest in the course of myocardial infarction - Martyna Kamińska; Sylwia Krzemińska (Kazimierz Wielki University, 2018)
Introduction: A sudden cardiac arrest is a condition, which directly threatens life, and there is a cessation of cardiac mechanical activity. This Life-threatening condition occurs when one ceases to function properly with the systems responsible for maintaining vital functions. Purpose .: Presenting the role of nurses in the care of patients after cardiac arrest in the course of myocardial infarction. Material and method: The method applied was that case study. Conclusions: The main problem of the patient after cardiac arrest were as follows- the possibility of re-cardiac arrest, shortness of breath, discomfort due to immobilization, depressed mood. During the nursing actions should eliminate the factors influencing the development of complications that can lead to death. The role of nurses is patient education aimed at improving the quality of life and reduce the risk of recurrence of cardiac arrest. Nursing care of the patient after cardiac arrest requires nurses to constantly extend knowledge, excellence and knowledge of the latest guidelines. Sudden cardiac arrest is a major challenge for modern medicine and should increase the scope of research on this issue.